Inhaled iloprost as part of combination therapy for persistent pulmonary hypertension of the newborn - Heru Samudro; Mulyadi M. Djer (Paediatrica Indonesiana, 2012)
Persistent pulmonary hypertension of thenewborn (PPHN) is rare, but life-threatening.If not treated, PPHN may cause respiratoryfailure and death in neonates. l,2,3 PPHNoften occurs in term or post-term infants with a historyof difficult labor, infection or asphyxia during birth.These infants do not have adequate oxygen duringlabor.3 Based on etiology, PPHN can be categorizedinto primary PPHN, which occurs by itself withoutapparent cause; or secondary PPHN, which is causedby meconium aspiration, hyaline membrane disease,neonatal sepsis with pneumonia, congenital heartabnormality, or maternal drug use (non-steroidalanti-inflammatories, methamphetamine, or selectiveserotonin re uptake inhibitors) during the thirdtrimester of pregnancy.